Seed dormancy and germination in different populations of the Argentinan endemic halophyte grass, Sporobolus phleoides (Poaceae: Chloridoideae) - Richard, Geraldina Alicia (2016)
Sporobolus phleoides Hack. is an endemic grass of Argentina that is considered an important genetic resource for saline environments. Knowledge of its germination behaviour is an indispensable requirement for the future potential use of this species. Thus, the effects of different factors on germination were evaluated in six representative populations collected from plants cultivated in a uniform environment. In addition, we investigated how the different parts of the seed contributed to dormancy and intraspecific variability. S. phleoides has non-deep physiological dormancy that appeared to be related to its testa. Thereby, dormancy was completely removed with puncturing treatments. High levels of germination were also obtained in seeds stratified at 8°C over 100 days in a solution of nitrates. After-ripening treatment did not have a significant effect in breaking dormancy. Similar germination behaviour and dormancy levels were observed in the different populations, especially when they were subjected to cold stratification. Although further work is needed, cold stratification appears to be the major factor in determining the time of seedling establishment in natural environments for this species.